Penerapan Pembelajaran Orang Dewasa oleh Instruktur Pelatihan Keterampilan Menjahit di SPNF SKB Lima Puluh Kota - Anila Putri Yuse; Jamaris Jamaris; Ismaniar Ismaniar (Universitas Negeri Padang, 2018)
This research is motivated by the success of Learning Activity Studio (SKB) in carrying out activities, this is seen from the application of instruction by instructors at SKB Lima Puluh Kota. The purpose of this study is to describe the application of adult learning by instructor in terms of views, learning experiences, selfconcept, and readiness to learn. The type of this research is quantitative descriptive research. The population in this study is residents learn training. Sampling technique in this research is simple random sampling from entire population. Data collection techniques used are questionnaires, while the questionnaire data collection tool. Technique of data analysis by using formula of percentage. From the results of the study showed that: instructorapply learning experiencesin the learning process, instructorapply self-concept in the learning process, instructor apply readiness to study in the learning process.